A Systematic Review of Museum Marketing Research: Key Insights and Future Research Directions - Tanja Komarac (Tržište, 2025)
Purpose – The purpose of this paper is to examine the current state of knowledge in the field of museum marketing. More precisely, the paper is aimed at investigating: 1) the advancements in the field of museum marketing and 2) the museum visitor experience as a key related concept. It seeks to identify potential obstacles hindering research and provide future research priorities. Design/Methodology/Approach – Data based on 1,153 papers from the Web of Science (Core Collection) database was subjected to bibliographic analysis using the VOSviewer (1.60) tool. For the purpose of systematic review, 65 papers were analyzed using ASReview LAB. The paper follows the PRISMA 2020 protocol for reporting systematic literature reviews. Findings and implications – The results of the bibliographic analysis reveal the complexities of the museum marketing field, which is studied in different fields outside marketing. The evident importance highlighted is that of tourism marketing journals, heritage, and arts management journals. Also, there are apparent clusters of collaboration among authors, as well as co-occurrence among author keywords used in the papers. The results of the systematic analysis identified six categories of the current research: 1) museum visitors, 2) technology in museum, 3) museum services, 4) learning and education, 5) authenticity, and 6) social media. Limitation – The limitations are related to the analysis period (from 1994 to 2024) since a few scientific papers were published before that period. Only data from the Web of Science (Core Collection) available in English was used. Also, the analysis relies on ASReview, which is a Python-based software. Originality – The paper provides the first systematic insight into thirty years of research in the museum marketing field.